PEMBUATAN ALAT PERAGA MATEMATIKA DARI LIMBAH BAHAN ALAM DI DESA SIALOGO KABUPATEN TAPANULI SELATAN - Masdelima Azizah Sormin; Jumaita Nopriani Lubis; Melvariani Syari Batubara; Lia Rosliana Dalimunthe; Bima Sakti; Sakila Manullang (Smart Education, 2025)
Abstract: This Community Service (PKM) focuses on efforts to improve the quality of mathematics learning in Sialogo Village, South Tapanuli Regency, through the utilization of natural waste materials. The aim of this activity is to empower teachers and parents in creating affordable, creative, and contextual mathematics teaching aids by utilizing neglected local resources. The implementation method includes three main stages: (1) Identification and socialization, namely a needs survey and introduction to the concept of teaching aids from waste; (2) Training and mentoring, where participants are invited to directly design and make teaching aids such as